Empowering Poor Communities Through Family Economic Assistance for PKH Recipients in Kebon Jayanti Village, Bandung City - Sri Damayanti; Pahruroji Pahruroji; Nada Jingga; Nindya Virginia (Pustaka Digital Indonesia, 2025)
The urgency of improving digital-based public service delivery is increasingly recognized, especially as local governments face pressure to provide fast, transparent, and efficient services. This study seeks to design an integrated public service information system that supports better data utilization in local government services. The research method used is Design Science Research (DSR), which includes six stages: problem identification, defining objectives of a solution, design and development, demonstration, evaluation, and communication. The population in this study includes all service activities within the Department of Population and Civil Registration in Barru Regency. The sample consists of 15 staff members, selected purposively based on their direct involvement in service processes and experience with existing digital systems. Data were collected through interviews, questionnaires, and the analysis of internal service documents such as Standard Operating Procedures (SOP), service logs, and policy reports. The instruments used in this research include semi-structured interview guides, user satisfaction questionnaires with Likert scales, and system evaluation tools based on the ISO 25010 quality model. The analysis involved both qualitative and quantitative approaches: content analysis was applied to interview transcripts and document data, while descriptive statistics were used to interpret user satisfaction scores and system usability metrics. The results show that the designed system improves service efficiency, reduces data redundancy, and increases user satisfaction. This study contributes to local digital transformation efforts by providing a practical system model that integrates fragmented public service data into a more cohesive and accessible platform.